2013
DOI: 10.21157/j.ked.hewan.v7i2.931
|View full text |Cite
|
Sign up to set email alerts
|

Injeksi Media Kultur Embrio Supernatan Dalam Uterus Untuk Meningkatkan Angka Implantasi Embrio Pada Mencit

Abstract: ABSTRAKPenelitian ini bertujuan mengetahui pengaruh injeksi media kultur embrio supernatan ke dalam uterus mencit 2 hari sebelum transfer embrio (TE) terhadap angka implantasi, yang diindikasikan oleh adanya embrio dan leukemia inhibitory factor (LIF) pada uterus. Mencit jenis Swiss Albino dibagi menjadi 2 kelompok yakni kelompok perlakuan dan kelompok kontrol, masing-masing terdiri atas 30 mencit. Kelompok perlakuan mendapat injeksi media kultur embrio supernatan (MKES) dalam uterus 2 hari sebelum TE sedangka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…LIF plays a role in the endometrial function of humans and domestic species. Furthermore, it has been suggested that LIF mRNA and protein are expressed in glands in the endometrium during the luteal phase of the menstrual cycle when implantation is about to occur [21].…”
Section: Role Of Cytokinesmentioning
confidence: 99%
See 4 more Smart Citations
“…LIF plays a role in the endometrial function of humans and domestic species. Furthermore, it has been suggested that LIF mRNA and protein are expressed in glands in the endometrium during the luteal phase of the menstrual cycle when implantation is about to occur [21].…”
Section: Role Of Cytokinesmentioning
confidence: 99%
“…This situation is stimulated by estrogen with progesterone in the culture of endometrial epithelial cells. This suggests that a high likelihood of low levels of potential antagonists regulating activation of the membranebound IL-6 family receptors [21].…”
Section: Role Of Cytokinesmentioning
confidence: 99%
See 3 more Smart Citations